2022
DOI: 10.1302/0301-620x.104b10.bjj-2022-0286.r1
|View full text |Cite
|
Sign up to set email alerts
|

Tourniquet use in patients undergoing tumour resection and endoprosthetic reconstruction of the knee

Abstract: Aims The aim of this study was to determine the prevalence and impact of tourniquet use in patients undergoing limb salvage surgery with endoprosthetic reconstruction for a tumour around the knee. Methods We retrieved data from the Prophylactic Antibiotic Regimens in Tumor Surgery (PARITY) trial; specifically, differences in baseline characteristics, surgical details, and postoperative functional outcomes between patients who had undergone surgery under tourniquet and those who had not. A linear regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…However, the group with greater trochanter preservation had lower dislocation rates. Gazendam et al reviewed patients undergoing a limb-salvage surgical procedure and endoprosthetic reconstruction around the knee and evaluated the utility of intraoperative tourniquet use 7 . They demonstrated that the use of an intraoperative tourniquet was associated with better early functional outcome, as well as a shorter operative time and a reduced length of hospital stay.…”
Section: Oncologic and Functional Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the group with greater trochanter preservation had lower dislocation rates. Gazendam et al reviewed patients undergoing a limb-salvage surgical procedure and endoprosthetic reconstruction around the knee and evaluated the utility of intraoperative tourniquet use 7 . They demonstrated that the use of an intraoperative tourniquet was associated with better early functional outcome, as well as a shorter operative time and a reduced length of hospital stay.…”
Section: Oncologic and Functional Outcomesmentioning
confidence: 99%
“…The Prophylactic Antibiotic Regimens in Tumor Surgery (PARITY) Randomized Controlled Trial Secondary Analysis Supplement The PARITY trial was published online in January 2022, and the data set was opened to all investigators to perform secondary analyses 70 . A total of 13 PARITY secondary analyses were recently published in a JBJS Supplement [71][72][73][74][75][76][77][78][79][80][81][82][83] . These important studies address several exploratory questions, including, among others, the risk factors for surgical site infection and reoperations following lower-extremity endo-prosthetic reconstruction, functional outcomes in pediatric patients compared with adult patients, the use of opioids in the orthopaedic oncology population, the use of negative-pressure wound therapy and postoperative drains and the risk for surgical site infection, the risk of thromboembolism following lower-extremity endoprosthetic reconstruction, and biopsy types and their effect on surgical variables and outcomes.…”
Section: Intraoperative Fluorescence Guidancementioning
confidence: 99%